2021
DOI: 10.1186/s13059-021-02331-0
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 lncRNA splice isoform promotes lung adenocarcinoma progression via enhancing c-Myc activity

Abstract: Background Although using a blockade of programmed death-ligand 1 (PD-L1) to enhance T cell immune responses shows great promise in tumor immunotherapy, the immune-checkpoint inhibition strategy is limited for patients with solid tumors. The mechanism and efficacy of such immune-checkpoint inhibition strategies in solid tumors remains unclear. Results Employing qRT-PCR, Sanger sequencing, and RNA BaseScope analysis, we show that human lung adenocar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 51 publications
(34 reference statements)
1
46
0
Order By: Relevance
“…sPD-L1 can arise from a non-proteolytic process, via an alternative splicing. The PD-L1 gene (and corresponding PD-L1 pre-mRNA) can generate many different splice variants, including a long non-coding RNA isoform (PD-L1-lnc) [ 100 , 101 ] and a variety of variants leading to truncated proteins. These isoforms have been shown to play distinct roles in the regulation of immune surveillance and progression in colorectal cancer [ 102 , 103 ].…”
Section: Generation Of Soluble Pd-l1: Proteolysis and Alternative Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…sPD-L1 can arise from a non-proteolytic process, via an alternative splicing. The PD-L1 gene (and corresponding PD-L1 pre-mRNA) can generate many different splice variants, including a long non-coding RNA isoform (PD-L1-lnc) [ 100 , 101 ] and a variety of variants leading to truncated proteins. These isoforms have been shown to play distinct roles in the regulation of immune surveillance and progression in colorectal cancer [ 102 , 103 ].…”
Section: Generation Of Soluble Pd-l1: Proteolysis and Alternative Splicingmentioning
confidence: 99%
“…Different studies have indicated that sPD-L1 is a functional, glycosylated protein, capable of binding to PD-1 [ 127 ]. There are engineered variants of sPD-L1 (generated with directed molecular evolution) with an affinity over 20 folds greater than that of native human PD-L1 and able to compete with an anti-PD-1 antibody [ 101 ]. In this study, native human sPD-L1 was found to induce suppressive effects on activated T-cells, thus mimicking the effect of mPD-L1 [ 128 ].…”
Section: Significance Of Soluble Pd-l1 In Cancermentioning
confidence: 99%
“…LncRNA was reported that as an miRNA sponge to competitively binding miRNA and result in change the expression of downstream target genes. For example, the PDL1 related lncRNA was shown that through elevated the c-Myc expression and participate in the progression of lung adenocarcinoma (Qu et al, 2021). Chen et al (2020) found that LINC00173.v1 via inhibits the miR-511-5p to upregulation of VEGFA expression, result in boost the vascular endothelial cells growth and migration in lung squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies employing gene silencing technology have been proposed to upregulate the tumor suppressive effects of lncRNAs, including Antisense oligonucleotides (ASOs), RNA interference (RNAi), and CRISPR/Cas9 (107). ASOs can attenuate the pro-tumor functions of lncRNA strands by directly binding to them and exhibit a synergistic anti-tumor effect in clinical studies when combined with RNAi technology (108), chemotherapeutic drugs (38), small molecule inhibitors (109), immune checkpoint antibodies (110), etc., which means lncRNA could be the appropriate targets for lung cancer treatment.…”
Section: Conclusion and Expectationsmentioning
confidence: 99%